2018
DOI: 10.22159/ijpps.2018v10i3.23961
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Phytochemical and Antibacterial Action of Himalayan Medicinal Herbs Peristrophe Bicalyculata Leaves Extract Against Respiratory Tract Pathogens

Abstract: Objective: Evaluate the antioxidant, phytochemicals and antibacterial screening of leaves extracts of Peristrophe bicalyculata.Methods: The antibacterial activity against the respiratory tract pathogens i.e., Staphylococcus aureus (MTCC 1144), Streptococcus pneumoniae (MTCC 655), Streptococcus pyogenes (MTCC 442), Pseudomonas aeruginosa (MTCC 2474) and Klebsiella pneumoniae (MTCC 4030) was examined by the method agar well diffusion and the minimum inhibitory concentration (MICs) was determined by the method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The corresponding ABTS radical scavenging activity was used for detection of the antioxidant activity. ZnO/CdS nanocomposites was the most active [30]. ZnO NPs caused decreased antioxidant enzyme activities as an antioxidant agent by inhibiting the formation of ROS and scavenging the free radicals [32].…”
Section: Free Radical Scavenging Methods (Abts)mentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding ABTS radical scavenging activity was used for detection of the antioxidant activity. ZnO/CdS nanocomposites was the most active [30]. ZnO NPs caused decreased antioxidant enzyme activities as an antioxidant agent by inhibiting the formation of ROS and scavenging the free radicals [32].…”
Section: Free Radical Scavenging Methods (Abts)mentioning
confidence: 99%
“…The free radicals of "2, 2'-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid)" (ABTS) were used for exposure of the antioxidant activity of ZnO NPs and ZnO/CdS nanocomposites. The decrease in color intensity was expressed as inhibition percentage [29,30]. The lower the percentage inhibition, the higher the antioxidant scavenging activity.…”
Section: Free Radical Scavenging Methods (Abts)mentioning
confidence: 99%
“…Ascorbic acid equivalents were determined using the standard graph of ascorbic acid. Butylated hydroxyanisole (BHA) was used as reference standard (Table 3) [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Another study conducted by Giwa OE et al found that ethanolic extract of Peristrophe bicalyculata leaves inhibited growth of Staphylococcus aureus, Klebsiella spp., Pseudomonas aeruginosa, Aspergillus niger, Aspergillus clavatus and [38] Rhizopus stolonifer . Chloroform extract of Peristrophe bicalyculata also demonstrated and was found significant anti-bacterial property against Staphylococcus aureus (MTCC 1144) (26±0.66 mm) and lowest inhibition against K. pneumonia (MTCC 4030)(18.3±0.79 mm) [39] Antioxidant activity A study conducted by Arya P (2018) showed that methanolic leaves extract of Peristrophe bicalyculata has potent DPPH free radical scavenging ability in comparison to other [39] extracts . Victor DS et al performed a comparative in vitro study regarding antioxidant properties between Ocimum gratissimum, Vitex doniana, Carica papaya and Peristrophe bicalyculata using DPHH free radical scavenging activity.…”
Section: Anti-bacterial Studymentioning
confidence: 98%